2016
DOI: 10.1371/journal.pone.0168649
|View full text |Cite
|
Sign up to set email alerts
|

Validation of EGCRISC for Chronic Hepatitis C Infection Screening and Risk Assessment in the Egyptian Population

Abstract: Chronic HCV infection, a highly endemic disease in Egypt, is usually asymptomatic for decades after infection. Prediction questionnaire tool was proofed to be a valuable, feasible and efficient instrument for the screening of several diseases. We previously developed an Egyptian HCV risk screening tool (EGCRISC). This study aims to validate/modify EGCRISC. A cross-sectional study testing 4579 individuals by EGCRISC as well as ELISA/PCR was performed. The sample was a stratified cluster sampling from urban and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…An informed written consent was signed by all participants invited after elaborating on the study aim and concerns. They were interviewed using a modified version of EGCRISC that inquires about factors associated with HCV antibody in Egypt [10, 11, 12]. Although the EGCRISC has four versions that are based on age and gender, we combined all questions in one sheet and added questions regarding visiting dentist and HCV status and treatment.…”
Section: Methodsmentioning
confidence: 99%
“…An informed written consent was signed by all participants invited after elaborating on the study aim and concerns. They were interviewed using a modified version of EGCRISC that inquires about factors associated with HCV antibody in Egypt [10, 11, 12]. Although the EGCRISC has four versions that are based on age and gender, we combined all questions in one sheet and added questions regarding visiting dentist and HCV status and treatment.…”
Section: Methodsmentioning
confidence: 99%
“…A face-to-face interview was conducted to fill the EGCRISC form with the predetermined cut-off points and zone limits: green, yellow and red zones for low-, intermediate- and high-risk individuals, respectively. Other potential risk factors were also inquired about [8, 11].…”
Section: Methodsmentioning
confidence: 99%
“…Due to the long asymptomatic phase of HCV infection, early detection is the challenge in HCV control. This can only be achieved through screening [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(57) An effective risk-based HCV screening tool tailored to Egyptians (EGCRISC) has been developed, validated and showed a good performance. (58)(59)(60) The cost analysis of EGCRISC use as a screening tool versus mass screening showed that, applying EGCRISC would save LE 0.44 billion accounting for about 21 646 227 unnecessary tests and would only miss about 69 660 cases. This estimation is based on a minimal cost of 20 L.E./test and the population census in January 2015 and did take into account the population growth.…”
Section: ✓ Social and Community Challengesmentioning
confidence: 99%